Productivity of women farmers in the derived savannah zone of Nigeria:Panacea to food crisis (2010)
"There is food crisis in Nigeria. Food supply can no longer meet up with food demand. Since Women Farmers are the major food producers in Nigeria, it implies that their productivity is significantly low. This study therefore, explored the potential for improving productivity of women farmers in the Derived Savannah Zone of Nigeria. Primary data were collected using multi-stage random sampling technique. Kogi and Kwara states were randomly selected from the six states in the zone. Following this was a random selection of two ADP administrative zones from each slate. A random selection of four LGAs was then made, one from each ADP stratum from which four villages were selected per LGA. In the final stage 200 respondents were randomly selected from the villages on the basis of probability proportionate to size. Data were collected on socio-economic and demographic characteristics, institutional factors, quantities and prices of inputs and outputs. Data were analysed using Descriptive Statistics, Total Factor Productivity Analysis (IFP), and Ordinary Least Squares Regression (OLS) Analysis. The mean age and farming experience of the women farmers were 47.6 ± 9.5 and 20.4± 12.3years respectively. Their mean farm size and number of plots cultivated were 1.8 ± 1.18 acres and 2.0 ± 0.84 respectively. Total factor productivity index ranged from 2.7 to 1,J 04.6 with a mean of 489.9 indicating low productivity level. Factors found contributing to low productivity include; year of farming .extension and land fragmentation. A unit increase in years of education and MEO would increase productivity level by 0.8872 (p<0.01) and 0.1061 (p<O.05) while year of farming, extension and number of plots decrease productivity level by .0069 (p<0.05) ,0.4092(p<0.05) 17.4419 and 0.6452 (p<0.1) respectively "